Compiling concurrency correctly: verifying software transactional memory - Hu, Liyang (2013)
Concurrent programming is notoriously difficult, but with multi-core processors becoming the norm, is now a reality that every programmer must face. Concurrency has traditionally been managed using low-level mutual exclusion /locks/, which are error-prone and do not naturally support the compositional style of programming that is becoming indispensable for today's large-scale software projects.